Incorporating information literacy in the Croatian school environment - Banek Zorica, Mihaela (Array, 2011)
Despite the relevance, potential and impact of IL activities on the wider social and pedagogical context, libraries in Croatia are lagging far behind the emerging global information literacy movement. Due to the general lack of written and widely published educational programs, mission statements or policies of Information Literacy on a national level, the majority of school libraries in Croatia are forced to provide only simple and most fundamental forms oriented more towards library and not information literacy. Diagnosing the emerging problem and trying to find a solution to the problem presented an idea for a pilot project. Educating the educators i.e. school librarians was set as a starting point in implementing information literacy in the educational environment. Results of the pilot project carried out with the Education and Teacher Training Agency in advocating information literacy in the school environment are presented in this paper. Research on the theory of current education problems together with research on best case scenarios was used as a foundation for creating learning materials and organizing a series of workshops for educating school librarians. Future plans for expanding the project with all participants of the educational process (principals, teachers and school librarians) are discussed and key elements of possible information literacy program are defined.